A mixed methods study of stakeholders' practices and attitudes on avian influenza H7N9 vaccination for the yellow broiler industry in Guangxi, China. Issue 4 (24th August 2021) - Tang, Hao; Shen, Chaojian; Zou, Lianbin; Cai, Chang; Wang, Youming; Robertson, Ian D.; Edwards, John; Huang, Baoxu; Bruce, Mieghan
Abstract: In response to a sudden increase in H7N9 human infections, China introduced an H5/H7 bivalent inactivated vaccine for poultry in Guangxi and Guangdong provinces in July 2017, which subsequently became integrated into the existing compulsory national H5N1 vaccination programme from September 2017. Although the vaccination programme effectively reduced H7N9 infections in humans and poultry, there are ongoing arguments against continuing this long‐term vaccination. These discussions have drawn policymakers to think about the possibility of stopping routine vaccination for H7N9 avian influenza viruses (AIVs) in China; however, they have not considered the poultry industry stakeholders' practices on and attitudes towards this vaccination. This study investigated H7N9 vaccination practices in the yellow broiler industry in Guangxi and stakeholders' attitudes on H7N9 vaccination, using a mixed methods design. The study found H7N9 vaccination was well adopted in the yellow broiler industry in Guangxi regardless of the source of the vaccines. Most stakeholders believed vaccination was the best measure to control H7N9 and H5N1 AIVs, and they showed a strong willingness to continue with vaccination even without government subsidies or freely provided vaccines. The motivations by stakeholders for using vaccines to control H7N9 and H5N1 were different due to the epidemiological differences between the two strains. Understanding poultry industry stakeholders' practices and attitudes on H7N9 vaccination has important practical implications in planning vaccination policies, particularly when considering the possibility of vaccination withdrawal.